2021
DOI: 10.1021/acsami.1c08127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Doping Ni on the Microstructures and Thermoelectric Properties of Co-Excessive NbCoSn Half-Heusler Compounds

Abstract: The half-Heusler (HH) compound NbCoSn with 18 valence electrons is a promising thermoelectric (TE) material due to its appropriate electrical properties as well as its suitable thermal and chemical stability. Nowadays, doping/substitution and tailoring of microstructures are common experimental approaches to enhance the TE performance of HH compounds. However, detailed theoretical insights into the effects of doping on the microstructures and TE properties are still missing. In this work, the microstructure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Doping is an effective approach to enhance the zT , since the electronic and thermal transport properties can be improved simultaneously by introducing point defects. [ 14,15 ] Further, heavy band semiconductors, including HH compounds, require high doping concentrations to optimize the electronic transport properties, which could be an advantage to realize a further reduction in the κ L owing to the high degree of atomic disorder. [ 16 ] For example, a recent study by Liu et al showed that the zT value of the Hf‐doped Ti 2 FeNiSb 2 DHH compound increased to ≈0.7 and ≈1.0 for n‐type and p‐type samples, respectively, by optimizing the carrier concentration and reducing the κ L by Fe and Ni doping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping is an effective approach to enhance the zT , since the electronic and thermal transport properties can be improved simultaneously by introducing point defects. [ 14,15 ] Further, heavy band semiconductors, including HH compounds, require high doping concentrations to optimize the electronic transport properties, which could be an advantage to realize a further reduction in the κ L owing to the high degree of atomic disorder. [ 16 ] For example, a recent study by Liu et al showed that the zT value of the Hf‐doped Ti 2 FeNiSb 2 DHH compound increased to ≈0.7 and ≈1.0 for n‐type and p‐type samples, respectively, by optimizing the carrier concentration and reducing the κ L by Fe and Ni doping.…”
Section: Introductionmentioning
confidence: 99%
“…Doping is an effective approach to enhance the zT, since the electronic and thermal transport properties can be improved simultaneously by introducing point defects. [14,15] Further, heavy DOI: 10.1002/aesr.202100206 Double half-Heuslers comprising two aliovalent half-Heuslers are promising candidates for thermoelectric materials because of their intrinsically low lattice thermal conductivity; however, poor electronic transport properties need to be overcome. Herein, the effects of Sn doping on the electronic and thermal transport properties of p-type Ti 2 FeNiSb 2 to enhance the thermoelectric performance via the compositional tuning route are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…LaPtSb, LaRhTe, BaBiK, and CdPNa have κ md,gb ≤ 1.2 W/Km, comparable to well-known low LTC thermoelectric materials such as PbTe [95,96] and SnSe [10,97]. This value is similar to or even lower than κ e in several doped HHs [80], e.g., κ e = 1.4 W/Km for NbCo 0.94 Ni 0.06 Sn [98] and κ e = 1.5 W/Km for ZrPtSn 0.92 Sb 0.0.08 [99]. Thus, with the identification of low LTC comparable to κ e , emphasis can shift to design strategies that reduce κ e .…”
Section: Discussionmentioning
confidence: 51%
“…Compared with the NbFeSb sample (Jeong et al, 2021), the σ values of all the samples were higher across all temperatures, while 3D, 4D, and 5D samples exhibited higher σ values than the NbCoSn sample (Yan et al, 2021). NbFeSb exhibited positive S values indicating ptype behaviour, while NbCoSn exhibited negative S values indicating n-type behaviour.…”
Section: Microstructure Evolution With Sn Content Under the Dry Milli...mentioning
confidence: 79%
“…The 5D sample, with a rising slope of the σ value, demonstrated metallic and n-type behaviour. Moreover, owing to a higher metallic phase than the semiconducting phase in the 5D sample, lowering of carrier mobility might have led to lower σ values in the 5D sample as compared to the 3D sample at temperatures below 600 K. This sort of lowering of carrier mobility beyond certain metallic (FH) phase content can be seen in NbCoSn with excess Co content and Ni doping (Yan et al, 2021). In the other samples, a clear bipolar transition due to the activation of holes around 700 K was observed (Chauhan et al, 2020;Ferluccio et al, 2018;Yang et al, 2022b).…”
Section: Microstructure Evolution With Sn Content Under the Dry Milli...mentioning
confidence: 98%